‘I THINK MY TEACHER NEEDS A CHANGE’: A REFLECTIVE EXPLORATION ON THE PRACTICUM OF PROSPECTIVE TEACHERS OF ENGLISH - Aslan, Ayça; Taş, Tunay (International Online Journal of Education and Teaching, 2024)
The teaching practicum is a valuable source of experience for prospective teachers of English. This study investigates types of practicum-based experiences through a thematic qualitative analysis on 24 participants’ written reflective reports collected over a ten-week period. Findings show that prospective teachers form their practicum experiences primarily based on three dimensions: (a) learning environment, (b) mentor teachers, and (c) students. Themes emerging from these dimensions have been found to include both positive and negative aspects according to participants’ reflective viewpoints. Consequently, it is discussed that how these modular experiences interrelate with each other is important for understanding what affordances practicum can offer to prospective teachers of English.